Sikap Petani Padi terhadap Penggunaan Combine Harvester di Kecamatan Paron Kabupaten Ngawi - Sindy Icha Mardiana; Emi Widiyanti; Eksa Rusdiyana (AGRITEXTS: Journal of Agricultural Extension, 2024)
The increasingly advanced development of agricultural technology in Indonesia leads to agricultural modernization. The technology currently developing in Indonesia, especially in terms of harvesting rice plants, is the combine harvester. Many farmers already use combines, one of which is the people of Jambangan and Ngale Villages, Paron Sub-district, Ngawi Regency. Using a combine harvester can provide benefits for farmers, especially in terms of efficiency in harvesting rice crops. This research aims to 1) find out the impact of using the combine harvester machine; 2) analyze the attitudes of rice farmers towards using the combine harvester machine; 3) analyze the factors that influence the attitudes of rice farmers towards using the combine harvester in Paron Sub-district, Ngawi Regency. The research method uses a quantitative approach with survey techniques. The sample consisted of 43 people and was determined using proportional random sampling. Data analysis uses multiple linear regression analysis. The results of the research show 1) the positive impact of using combine harvester technology in increasing harvest efficiency while the negative impact is resulting in soil density and a reduction in labor labor for harvesting up to 92%; 2) the attitude of rice farmers towards the use of combine harvesters is in the strongly agree category with a percentage of 80.12%; 3) the results of the analysis of factors that influence the attitudes of rice farmers towards the use of combine harvesters in Paron Sub-district, Ngawi Regency show that non-formal education and experience have a significant influence.